A MATLAB program for the computation of the confluent hypergeometric function Φ2 - Martos-Naya, Eduardo; Romero-Jerez, Juan Manuel; López-Martínez, Francisco Javier; París-Ángel, José Francisco (My University, 2016)
We here present a sample MATLAB program for the numerical evaluation of the confluent hypergeometric function Φ2. This program is based on the calculation of the inverse Laplace transform using the algorithm suggested by Simon and Alouini in their reference textbook [1].
Keywords: Laplace, Transformación de; Laplace inverse transform; Confluent hypergeometric function